2018
DOI: 10.1155/2018/2024835
|View full text |Cite
|
Sign up to set email alerts
|

Ballroom Dancing Promotes Neural Activity in the Sensorimotor System: A Resting-State fMRI Study

Abstract: Objective This study aims at investigating differences in the spontaneous brain activity and functional connectivity in the sensorimotor system between ballroom dancers and nondancers, to further support the functional alteration in people with expertise. Materials and Methods Twenty-three ballroom dancers and twenty-one matched novices with no dance experience were recruited in this study. Amplitude of low-frequency fluctuation (ALFF) and seed-based functional connectivity, as methods for assessing resting-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Compared with non-dancers, female ballet dancers showed decreased GM volumes in the left supplementary, premotor, and motor cortices, as well as the putamen and superior frontal gyrus, decreased WM volumes in both internal capsules, both corticospinal tracts, the corpus callosum, and the left anterior cingulum; and reduced FA in the WM underlying bilateral premotor cortices (Hänggi, 2010 ). Recently, Lu et al ( 2018 ) found that ballroom dancers, as compared to novices, demonstrated reduced ALFF in the left lingual gyrus; elevated ALFF in the bilateral IFG, bilateral precentral gyrus, left inferior temporal gyrus, left middle temporal gyrus, left middle frontal gyrus, left postcentral gyrus, right superior temporal gyrus (STG), and right middle occipital gyrus; and altered FC among parietal and temporal areas and the IFG.…”
Section: Occupational Neuroplasticitymentioning
confidence: 99%
“…Compared with non-dancers, female ballet dancers showed decreased GM volumes in the left supplementary, premotor, and motor cortices, as well as the putamen and superior frontal gyrus, decreased WM volumes in both internal capsules, both corticospinal tracts, the corpus callosum, and the left anterior cingulum; and reduced FA in the WM underlying bilateral premotor cortices (Hänggi, 2010 ). Recently, Lu et al ( 2018 ) found that ballroom dancers, as compared to novices, demonstrated reduced ALFF in the left lingual gyrus; elevated ALFF in the bilateral IFG, bilateral precentral gyrus, left inferior temporal gyrus, left middle temporal gyrus, left middle frontal gyrus, left postcentral gyrus, right superior temporal gyrus (STG), and right middle occipital gyrus; and altered FC among parietal and temporal areas and the IFG.…”
Section: Occupational Neuroplasticitymentioning
confidence: 99%
“…ALFF is a feasible and reliable indicator of resting-state regional brain activity, 41 which is altered in the presence of brain lesions. 12,43 ALFF has been used to measure diverse brain plasticity, including the sensorimotor system, 23 motor recovery, 21 reorganization of cerebro-cerebellar circuits, 43 and functional networks. 19 Altogether, this suggests that ALFF is a reliable tool to investigate brain disorders and the concomitant functional plasticity.…”
mentioning
confidence: 99%
“…Altered functional connectivity has also been found in dancers in several studies (Burzynska et al, 2017a;Hackney and Earhart, 2009;Li et al, 2015;. In (Lu et al, 2018), expert ballroom dancers had altered functional connectivity between the inferior frontal gyrus and temporal/parietal regions, but novice dancers did not. In (Burzynska et al, 2017a), dancers had greater functional connectivity between the thalamus and the frontal pole.…”
Section: Changes In Brain Structure Following Dance Trainingmentioning
confidence: 70%
“…In (Lu et al, 2018) activity in sensorimotor regions than novice dancers, as well as "functional alterations in frontal-temporal and frontal-parietal connectivity" (Lu et al, 2018). These changes may well reflect the learning of skills needed for dancing, such as "action perception, attentional control, and movement adjustment" (Lu et al, 2018).…”
Section: Resting State Neural Activitymentioning
confidence: 99%
See 1 more Smart Citation